Isolated Retrobulbar Hydatid Cyst: A Case Report - Sali, Shahnaz; Minooeifar, Javad; La'li, Azadeh; Doosti, Zahra; Ebrahimi, Masoud (Novelty in Biomedicine, 2018)
Background: Hydatid cyst is caused by Echinococcus granulosus and human is the accidental host. The most common sites of involvement are the liver and lungs, and involvement of other organs is less common. Ocular involvement of hydatid cyst is one of the most uncommon manifestations of hydatid cyst. Cases Report: The case was a 40-year-old woman with a retrobulbar cystic lesion who was examined for the left eye pain and then proptosis. With the initial diagnosis of retrobulbar tumor, the patient underwent surgery and the removed mass was sent to the pathology laboratory. Since the result indicated the existence of a hydatid cyst, the patient was referred to the infectious service and was treated with albendazole. Conclusion: Although the ocular involvement of hydatid cyst is uncommon, it should be considered as a differential diagnosis in patients with proptosis in the endemic areas.